1979
DOI: 10.1021/jf60222a011
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of O,O,S-trimethyl and triethyl phosphorothioate to the rat

Abstract: Loss of /3-carotene was monitored from spectra over the range 350-520 nm of solutions of aliquots (about 100 mg) in light petroleum (10 mL). Pigment concentration was calculated from the absorbance at 450 nm assuming Elcm1% = 2500. Control experiments were carried on simultaneously by storing trays in the dark. Antioxidant effect of ethoxyquin (0.02%) was determined in methyl oleate solutions exposed to the light. LITERATURE CITED

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…Previous investigations reported that acute administration of OOS-TMP to rats leads to a delayed toxicity (death occurring 4 to 28 days after treatment). Symptoms of this delayed toxicity include body weight loss, and red staining around the eyes, nose and mouth [25][26][27]. Although the mechanism of this delayed toxicity remains unknown, histopathological and biochemical studies suggest that the lung may be a principle target organ of the delayed toxicity caused by OOS-TMP [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations reported that acute administration of OOS-TMP to rats leads to a delayed toxicity (death occurring 4 to 28 days after treatment). Symptoms of this delayed toxicity include body weight loss, and red staining around the eyes, nose and mouth [25][26][27]. Although the mechanism of this delayed toxicity remains unknown, histopathological and biochemical studies suggest that the lung may be a principle target organ of the delayed toxicity caused by OOS-TMP [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if a byproduct generated from OMT degradation retains the P@O bond, it still has an acute toxicity. For example, the oral LD 50 values in rats are 840 and 15 mg kg À1 for TMP and STMP, respectively (Mallipudi et al, 1979;Meister, 1991). The toxicity of STMP is two times as high as that of OMT (i.e., 30 mg kg À1 ) (NCILB, 1973).…”
Section: Toxicity Change Of Omt Solutionmentioning
confidence: 99%
“…The nontoxic ionic metabolites thus produced are readily excreted in the urine (March et al, 1956;Casida et al, 1963;Plapp and Tong, 1966;Talcott et al, 1979aTalcott et al, , 1979bTalcott et al, , 1979c. The recent discovery of the toxicity of some impurities in technical organophosphorus pesticides has led to reevaluation of the safety of several of these compounds (Mallipudi et al, 1979). In contrast to acute intoxication by an anticholinesterase organophosphate insecticide such as parathion, longer holding periods were required to determine LD SO values in rats treated with the impurities 0,0,5-trimethyl phosphorothioate and 0,0,5-triethyl phosphorothioate, particularly at lower doses.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mode of action of these delayed toxic compounds is not known, they were shown to inhibit carboxylesterases and cholinesterases (Mallipudi et al, 1979;Talcott et al, 1979c;Umetsu et al, 1980).…”
Section: Introductionmentioning
confidence: 99%